KAJIAN SENI ISLAM PADA MASJID HJ. SUDALMIYAH RAIS UNIVERSITAS MUHAMMADIYAH SURAKARTA - Umairoh, Siti; Nurjayanti, Widyastuti (Sinektika: Jurnal Arsitektur, 2018)
The mosque which is a place of worship or place of worship for Muslims is also the culmination of the sanctity of space in Islam and is an artifact of Islamic architecture. Islamic art forms on mosques are a blend of symbolic elements of Islamic architecture. Masjid Hj. Sudalmiyah Rais is a part of public facilities in Universitas Muhammadiyah Surakarta. The mosque has a very thick Islamic architectural style. This research will explore and find out what forms of Islamic art are applied to the mosque. The purpose of this study finds Islamic art was applied in the mosque and how to presents Islamic decorative arts found in the mosque. This study uses a qualitative descriptive method. This research carried out by seeing the object of the mosque, then assessed the parts that were based on the results of matching parameters of the symbolic elements of Islamic architecture. Masjid Hj.Sudalmiyah Rais fulfills 11 of these 12 parameters. The missing thing is the hand made decorations. That can be concluded that Masjid Hj. Sudalmiyah Rais applied Islamic art to the physical form of the building. Islamic ornamental arts contained in the mosque that are in the form of calligraphy ornaments, geometric ornaments, and flower ornaments (florist). The benefits of this research are to increase public knowledge about Islamic art studies found in Masjid Hj. Sudalmiyah Rais and gave references to Architects about the use of Islamic art in mosques.